Functional Testing of Web-Based Input Form Using Boundary Value Analysis Technique: A Case Study on TemanTernak - Akhmad Zufar Rafif; Muhammad Faris Fadhil Islam; Muhammad Nasir; Muhammad Rafi Alexander Prayoga; Raden Muhammad Raditya Rahman; Sofiyanti Indriasari (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Software reliability is highly dependent on robust data validation mechanisms to prevent data integrity issues. The main issue raised in this study is the risk of input errors in the "Create Doctor Invitation" form in the TemanTernak web application, which could potentially cause invalid data storage. This study aims to evaluate the quality of the system's input validation to ensure its compliance with the requirements specifications. The proposed solution is the implementation of Black Box Testing with the Boundary Value Analysis (BVA) technique. The testing methodology was carried out following the Software Testing Life Cycle (STLC) stages, in which 17 test scenarios were run to assess four critical elements: name and title, email, phone number, and invitation message. The test results revealed that the system only achieved a functional success rate of 41.2%. Although the application successfully processed standard valid inputs, the system failed to reject the majority of inputs that were outside the tolerance limits (off-boundary) and passed empty inputs in mandatory fields. In conclusion , the current validation mechanism is insufficient to handle extreme conditions. In the future, the implementation of strict server-side validation with range constraints is necessary to mitigate these vulnerabilities.